Performance investigation of a self-propelled foil with combined oscillating motion in stationary fluid. (1st March 2019) - Lin, Xingjian; Wu, Jie; Zhang, Tongwei
Abstract: The performance of a self-propelled foil in stationary fluid is numerically studied in this paper. To conduct the numerical simulations, an immersed boundary-simplified circular function-based gas kinetic method is used. The investigation first compares the self-propulsion performances of flapping foil with three different patterns, i.e., pure heaving motion, pure pitching motion, and combined oscillating motion. It is found that the combined oscillating foil generally outperforms the heaving foil. Whilst the heaving foil performs better than the pitching foil with the moderate motion frequency and amplitude. Moreover, the effects of Reynolds number, phase difference, and pivot location on the self-propulsion of the combined oscillating foil are also examined. The results obtained indicate that there exists a threshold value of Reynolds number, and below which the propulsion performance declines considerably. In addition, the phase difference can reverse the foil's auto-propelled direction. Furthermore, the pivot location near the center of mass can both reduce the power consumption and increase the efficiency significantly. The results obtained here may be utilized to optimize the design of propellers of micro aerial/underwater robots.